2015
DOI: 10.1021/acsami.5b04409
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Performance of All-Solid-State Li–Air Battery with SWCNTs/LAGP Cathode

Abstract: The all-solid-state Li-air battery has been fabricated, which is constructed by a lithium foil anode, a NASICON-type solid state electrolyte Li1+xAlyGe2-y(PO4)3 (LAGP) and single-walled carbon nanotubes (SWCNTs)/LAGP nanoparticles composite as air electrode. Its electrochemical performance was investigated in air atmosphere. Particularly, this battery exhibited a larger capacity about 2800 mAh g(-1) for the first cycle, while comparatively the battery with multiwalled carbon nanotubes (MWCNTs)/LAGP as cathode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 23 publications
1
72
0
2
Order By: Relevance
“…Studies have indicated that a lower resistance and a stable interface can result from melting the metal Li anode onto the NASICON-like LAGP solid electrolyte. [78,83] Similarly, the resistance between Li and garnet electrolyte LLZO fell dramatically from 5822 cm 2 to 514 Ω cm 2 after heating to 175 °C. [119] These results can be attributed to the better compatibility of the Li metal to the rough surface of the solid electrolyte after thermal heating.…”
Section: Interface Between Anode and Solid Electrolytementioning
confidence: 99%
See 3 more Smart Citations
“…Studies have indicated that a lower resistance and a stable interface can result from melting the metal Li anode onto the NASICON-like LAGP solid electrolyte. [78,83] Similarly, the resistance between Li and garnet electrolyte LLZO fell dramatically from 5822 cm 2 to 514 Ω cm 2 after heating to 175 °C. [119] These results can be attributed to the better compatibility of the Li metal to the rough surface of the solid electrolyte after thermal heating.…”
Section: Interface Between Anode and Solid Electrolytementioning
confidence: 99%
“…The first SSLAB was investigated in 2010, and the amount of related papers is currently limited. [77][78][79][80][81][82][83][84][85][86][87][88][89][90] Thus, we will focus on solid-state Li-air/O 2 batteries as well as the batteries using solid-state cathode with hybrid electrolyte.…”
Section: Progress and Prospects Of Cathodes For Solid-state Li-air Anmentioning
confidence: 99%
See 2 more Smart Citations
“…[11,12] Among these energy storage systems, Li-ion batteries have attracted attention because of their long cycling life and environmental-friendly properties. [14][15][16][17] In this article, nonaqueous Li-O 2 batteries will be discussed. [2,13] Recently, electric vehicles (EVs) have attracted attention owing to their zero-pollution property.…”
mentioning
confidence: 99%